The modern state : theories and ideologies - Cudworth, Erika, 1966- (Edinburgh University Press, 2007)
Broad ranging in its coverage of the liberal democratic state and other, non-democratic state formations, the book offers chapters on each of the core theories of the modern state. Each chapter is structured in the same way to allow for ease of cross-referencing and for comparisons to be drawn between theories, with parts on Context, Definition, Theorists and Practical Politics.There are chapters on:The Emergence of the Modern StateLiberalismElite TheoriesMarxismSocialismAnarchismConservatismFascismFeminismsThe New RightFundamentalismFutures The authors work on the premise that theory is relevant to everyday life, helping us to understand current political transitions and institutional formations and practices. Taking a practical view of politics, each chapter illustrates how state theory has been deployed in recent historical contexts and policy initiatives, using examples to bring the theory to life.Key Features Unique in considering the liberal democratic state and other, non-democratic state formationsIncludes a wide range of examples, such as Marxist states in Eastern Europe and non-secular, militarist and emergent democratic states in the developing worldCovers a wide theoretical range and includes less well-known ideas and approaches such as those of fundamentalism, fascism and anarchismShows how different theories of the state have affected the framing and implementation of policies, or the history of political parties and movements.